ChemInform Abstract: Highly Ligand‐Controlled Regioselective Pd‐Catalyzed Aminocarbonylation of Styrenes with Aminophenols. Issue 46 (27th October 2016) - Xu, Tongyu; Sha, Feng; Alper, Howard
Abstract: Different reaction conditions allow the regio‐ and chemoselective reaction of styrenes with para‐, meta, and ortho‐aminophenols and carbon monoxide to give a wide variety of amides.